Technological Advances in Seismic Data Processing and Imaging - Liu, Guofeng; Zhang, Zhifu; Meng, Xiaohong (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Seismic exploration is a geophysical method with deeper exploration capabilities and higher resolution than potential geophysical methods. It has been widely used in the fields of oil and gas, mineral, and environmental exploration, as well as engineering. This Special Issue provides several advanced methods and technologies for seismic data processing and interpretation, including the following: noise elimination, migration and inversion, passive seismic exploration, a theory for seismic wave propagation, and also Artificial Intelligence technology used in seismic data processing.